Implementation of E-Module Integrated Science Based on Joyful Learning with Breathing System Theme on Students’ Critical Thinking Skills and Learning Independency - Rahmawati, Ayu Ariana; Parmin, Parmin (Journal of Environmental and Science Education, 2021)
This research aims to determine the effect of e-module on students' critical thinking and learning independence development. The design of this research was quasi-experimental with a nonequivalent control group design. The sample was drawn using a random sampling technique with VIII D class as the experiment group and VIII C class as the control group. The data were collected through taking documentation data, tests, observation, and questionnaires. Using e-module was measured and analyzed by using t-test then descriptive analysis of observation and questionnaire. The research shows that t-test analysis to students' critical thinking skills is 10,77741 > 2,0003, meaning that there is a significant difference because tvalue > ttable. Meanwhile, for students' learning independency, it shows that r=0,9319 and the coefficient of determination of 86,84% mean that e-module has a positive effect on learning independency. Students also gave a good response of 83,87% so it can be concluded that e-module Integrated Science based on joyful learning was successfully affected' critical thinking skills and learning independency.